USING LINO.IT APPLICATION IN TEACHING ENGLISH - Bambang Triyono; An Fauzia Rozani Syafei (Journal of English Language Teaching, 2016)
In teaching English there are some common problems that found by the teacher in classroom, like students have lack motivation in learning English, teacher finds difficulty to choose an interesting method, a monotonous learning. Those problem make the students think that English as a difficult subject. Studying in the classroom is not limited with the use of paper, book or pen only. Using technology-based media and internet like application can be a good solution and give positive impact in teaching English. One of application based on the use of internet is Lino.it. Lino.it is software which formed in virtual wall and it can be placed some notes, pictures and videos. Teacher can use this software to support the use of black board or teacher can focus the teaching and learning with Lino.it. The writer wrote this paper with purpose: tell how teacher use Lino.it application in teaching process. The writer also hopes this application can make the teacher to be more creative in utilization media and develop the students’ learning quality.